The Universidad del Aire: Broadcasting Program and Tribune for the History of Cuba (1933-1953) - Relys Arango, Eliany (2023)
The article examines the contribution of the Universidad del Aire –radio broadcasting program created and directed by the intellectual Jorge Mañach Robato (1898–1961)– to the dissemination and socialization of Cuban history between 1933 and 1953. The objective is to reveal the main thematic lines of the radio lectures published in Cuadernos de la Universidad del Aire –an important editorial management parallel to the program. The use of the radio as a suitable vehicle to overcome the barriers of illiteracy is pondered, it is demonstrated that the program became a teaching institution not only for ha analysis and diffusion of past events, but also for the contemporaneity of country. A chronological and thematic index of the conferences and lectures related to the history of Cuba is provided.  Keywords: Broadcasting program, intellectuals, culture, scientific dissemination, historiography.